Stability of pyramidal traveling fronts in the degenerate monostable and combustion equations II. (June 2019) - Bu, Zhen-Hui; Ma, Lu-Yi; Wang, Zhi-Cheng
Abstract: This paper is concerned with the global stability of pyramidal traveling fronts for the reaction–diffusion equations with degenerate monostable and combustion nonlinearities. The existence and part of the stability of such fronts have been proved by constructing supersolutions and subsolutions in our works (Bu and Wang, 2017; Wang and Bu, 2016). In this paper we prove the global asymptotic stability of pyramidal traveling fronts. Our main technique is constructing new subsolutions coupled with the comparison principle.